1985
DOI: 10.1073/pnas.82.3.869
|View full text |Cite
|
Sign up to set email alerts
|

Association of the N-formyl-Met-Leu-Phe receptor in human neutrophils with a GTP-binding protein sensitive to pertussis toxin.

Abstract: Pertussis toxin inhibits the N-formyl-MetLeu-Phe (fMet-Leu-Phe) mediated human neutrophil functions of enzyme release, superoxide generation, aggregation, and chemotaxis. As pertussis toxin modifies the GTP binding receptor-regulatory protein "N1," the association of the fMetLeu-Phe receptor with such a protein was further examined in purified neutrophil plasma membranes. Both fMet-Leu-Phemediated guanine nucleotide exchange and nucleotide-mediated regulation of the fMet-Leu-Phe receptor are inhibited by pertu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(64 citation statements)
references
References 27 publications
2
62
0
Order By: Relevance
“…The involvement of a guanine nucleotide-binding protein (G protein) in neutrophil activation has been implicated from the inhibitory effect of pertussis toxin on the response stimulated by fMet-Leu-Phe (18,30). This G protein could have been directly activated by GTPTS in our experiments.…”
Section: Discussionmentioning
confidence: 74%
“…The involvement of a guanine nucleotide-binding protein (G protein) in neutrophil activation has been implicated from the inhibitory effect of pertussis toxin on the response stimulated by fMet-Leu-Phe (18,30). This G protein could have been directly activated by GTPTS in our experiments.…”
Section: Discussionmentioning
confidence: 74%
“…Evidence that these "classic chemoattractants" act on GPCRs first came from the observation that pertussis toxin (PTX) could alter the binding affinity of chemotactic formyl peptides [5] , a characteristic feature of certain GPCR ligands [6] . Working independently, two laboratories reported that PTX could block formyl peptide (eg, fMet-Leu-Phe, fMLF)-induced neutrophil functions through ADP-ribosylation of the Gi class of heterotrimeric G proteins [7,8] . These early studies demonstrate that the chemotactic peptide receptor functionally couples to a heterotrimeric G protein that is a substrate for ADP-ribosylation by PTX.…”
Section: Gpcrs That Mediate Cell Migration and Phagocyte Activationmentioning
confidence: 99%
“…In a pathological context such as tissue necrosis (not apoptosis), cellular contents are released extracellularly and can be perceived by other cells and phagocytes as "danger associated molecular patterns" or DAMPS [34]. Once the agonist binds, FPRs are phosphorylated and glycosylated, which initiates interaction with pertussis toxin-sensitive Gi proteins [35][36][37][38]. Ensuring cell signaling cascades involves MAPK and phosphatidylinositol 3-kinase (PI3K) pathway activation, which together with small GTPases initiate phagocytic functions such as stimulation of actin dynamics and chemotaxis, and the activation of ROS generation by NADPH oxidase enzyme (Nox2) in a process known as the respiratory burst [39][40][41].…”
Section: Epithelial Perception and Monitoring Of The Microbiotamentioning
confidence: 99%